Preliminary Checklist of The Herpetofauna of Pulau Besar, Melaka, Malaysia - Chan Kin Onn; L Lee Grismer; Perry Lee Wood Jr.; Jesse Leland Grismer; Norhayati Ahmad (Tropical Life Sciences Research, 2009)
A herpetological survey was conducted at Pulau Besar, Melaka from 10 to 12 June 2008, resulting in the discovery of five species of amphibians, nine species of lizards (including one new species of the gekkonid Cyrtodactylus) and one snake species. This report constitutes the first checklist of the herpetofauna of Pulau Besar and the Water Islands Archipelago. Satu tinjauan herpetofauna telah dijalankan di Pulau Besar, Melaka dari 10 hingga 12 Jun 2008. Hasil daripada tinjauan itu, lima spesies amfibia, sembilan spesies cicak (termasuk satu spesies baru gekkonid daripada genus Cyrtodactylus) dan satu spesies ular telah dijumpai. Ini merupakan laporan dan senarai spesies pertama mengenai herpetofauna di Pulau Besar dan Kepulauan Air.